FINANCING OPTIONS FOR SMALL AND MEDIUM ENTERPRISES (SMEs) IN NIGERIA - E. C. Gbandi; G. Amissah (European Scientific Journal, ESJ, 2014)
Small and Medium enterprises act as catalysts in the economic development of the developed and developing countries. Developing countries like Nigeria that require sustained economic growth in their economies must pay attention to the SME sector and harness the great potential to generate employment, improved local technology, output diversification, developed indigenous entrepreneurship and forward integration with large-scale industries that can be provided by the sector. Unfortunately, the SMEs in Nigeria have underperformed despite the fact that the SMEs in Nigeria constitute more than 90% of Nigerian businesses, their contribution to the nation’s GDP is below 10%. This very low percentage contribution of the SMEs to Nigeria’s GDP could be attributed to amongst others; unfriendly business environment, poor funding, low management skills and lack of assess to modern technology. However, this paper focuses on adequate funding which will take care of some of the problems such as provision of modern technology and low managerial skills. It examines the financing of SMEs in Nigeria and the various financing options available to the SMEs. This involved looking at debt financing by considering the role commercial, microfinance banks, co-operatives and other finance institutions play in the financing of SMEs in Nigeria. It also considered the role of equity financing through Venture capital and Business angels financing. It concluded that funding of SMEs in Nigeria is very critical if they are to perform their role of growth and development of the nation’s economy.